Task attributes and process integration in business process offshoring: A perspective of service providers from India and China - Luo, Yadong; Wang, S.; Zheng, Q.; Jayaraman, V. (Palgrave Macmillan, 2012)
This study addresses an important issue in designing and managing business process offshoring (BPO): process integration between an offshore service provider and its global BPO client. We applied the information-processing lens in global BPO and developed the logic that internationally disaggregated process integration requires a fit between process integration and BPO's task characteristics (i.e., task complexity and security) and task interdependence (task connectivity, stickiness, and dependency). This alignment is further moderated by the task context, such as the geographic dispersion of the global client's end-customers and the type of offshore provider (independent vendor vs captive and joint venture). Finally, we suggest that process integration has a positive but curvilinear relationship with the economic returns achieved by offshore providers. Our analysis of 308 BPO companies in India and China supports our propositions. We conclude that international managers monitoring and integrating globally disaggregated activities in BPO should establish a proper alignment with the BPO project's task traits and task interdependence, and look closely at the conditioning effect of external complexity. By redressing the paucity of research on governing global BPO, this study offers some insights into the integration-externalization dynamics for growing business/knowledge process offshoring.